2021
DOI: 10.3390/ijerph18094855
|View full text |Cite
|
Sign up to set email alerts
|

Korean Childcare Providers’ Knowledge, Attitudes, Concerns, and Practices of Febrile Convulsions

Abstract: With the increase in the number of childcare facilities, childcare providers’ coping skills to take quick action in emergencies have become crucial. This study was to examine Korean childcare providers’ knowledge, attitudes, concerns, and practices regarding febrile convulsions (FCs), and to identify factors influencing their management of FCs. A cross-sectional study was conducted using a questionnaire of 216 Korean childcare providers. Descriptive statistics were used to describe the sample characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…The study showed that the highest proportion of participants (n=12; 57.1%) corresponded to more than half or 5 years of nursing experience. The results of this study were consistent with those of a study that found that participants (n = 21;47.7%) had worked as a nurse in Egypt for less than 5 years (12) . The results of the current study were also consistent with a study conducted at the emergency department / Teaching Hospital in He Al-Nasiriyah.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study showed that the highest proportion of participants (n=12; 57.1%) corresponded to more than half or 5 years of nursing experience. The results of this study were consistent with those of a study that found that participants (n = 21;47.7%) had worked as a nurse in Egypt for less than 5 years (12) . The results of the current study were also consistent with a study conducted at the emergency department / Teaching Hospital in He Al-Nasiriyah.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, these results were in line with a research conducted in Alexandria, Egypt, that found the highest percentage of participants (n=24, or 33.8%) have a diploma in nursing (12) . The majority of the sample in the control group (52.4%) were nursing institute members, in contrast to a study conducted in that found the high majority of the sample (45.8%) to be nursing institute members (10) .…”
Section: Discussionsupporting
confidence: 90%
“…The literature shows that there are gaps in what the caregivers of children know and in the knowledge and practices of pediatricians and pediatric healthcare providers. Different aspects of the same problem have been reported in Korea [ 35 ], Iran [ 36 ], Turkey, the USA [ 37 ], Saudi Arabia [ 38 ], Iraq [ 39 ], India [ 40 ], Germany [ 6 ], and Japan [ 15 , 41 ] among other countries. The reports span across at least the last 15 years, showing that it an ongoing problem that can affect different populations at different times.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lack of knowledge causes false beliefs and inappropriate management of the situation (13). Inadequate knowledge of these conditions makes some panic when their child has a fever and become agitated when they cannot control it and its adverse effects (7).…”
Section: Introductionmentioning
confidence: 99%
“…Correct parental intervention during seizures, which will be possible with proper training, can prevent complications such as head injuries, mouth and teeth injuries, and suffocation during seizures (14). Therefore, training followed by increasing awareness can increase the understanding and ability to manage the situation and care for the child (8) and reduce parents' worries and negative attitudes toward febrile seizures (13). The most common thing that mothers do after experiencing a febrile seizure is to search for information.…”
Section: Introductionmentioning
confidence: 99%